Pelatihan Penanganan Cedera Ankle dengan Metode RICE (Rest, Ice, Compression, Elevation) pada Pelajar di SMPN 4 Ungaran - Nilawati, Ika; Guntur Ratih Prestifa Herdinata; Nasri; Fiore Elang Arsyandi; Deni Irwansyah (UNIVERSITAS NGUDI WALUYO, 2025)
Sports injuries are soft or hard tissue damage caused by impact, physical activity that exceeds the training load limit, which can cause pain. Proper handling of sports injuries is expected not to deepen damage to body tissue. The purpose of this community service is to provide education and training on handling ankle injuries with the RICE method (Rest, Ice, Compression, Elevation), so that it can increase knowledge about sports injuries and, at the same time, handle ankle injuries in students. This activity was carried out at SMPN 4 Ungaran, Ungaran Barat District, Semarang Regency. Participants in this activity included 32 grade VIII students with the aim of forming independent characters in students. The methods used in this activity include several stages, namely the preparation stage, the activity implementation stage, and the monitoring and evaluation stage. The results of this community service activity showed an increase in the knowledge of class VIII students of SMPN 4 Ungaran regarding the handling of sports injuries, especially ankle injuries, using the RICE method (Rest, Ice, Compression, Elevation). Based on the evaluation data before and after the training, the following results were obtained: The number of participants in the good category increased by 59.3%, the number of participants in the sufficient category decreased by 46.8%, and the number of participants in the less category decreased by 12.5%. Based on the results of the activities that have been carried out, it can be concluded that educational and training activities regarding the handling of ankle injuries using the RICE method have succeeded in increasing the knowledge of class VIII students at SMPN 4 Ungaran. This training is effective in changing the understanding of participants from the less and sufficient categories to the good category. ABSTRAK Cedera olahraga merupakan adanya kerusakan jaringan lunak maupun keras yang diakibatkan adanya benturan, aktivitas fisik yang melebihi batas beban latihan sehingga dapat menimbulkan nyeri. Penanganan yang tepat dalam cedera olahraga diharapkan tidak memperdalam kerusakan pada jaringan tubuh. Tujuan dalam pengabdian kepada masyarakat ini adalah memberikan edukasi dan pelatihan tentang penanganan cedera ankle dengan metode RICE (Rest, Ice, Compression, Elevation), sehingga dapat meningkatkan pengetahuan tentang cedera olahraga dan sekaligus penanganan cedera ankle pada pelajar. Kegiatan ini dilaksanakan di SMPN 4 Ungaran Kecamatan Ungaran Barat Kabupaten Semarang. Peserta dalam kegiatan ini meliputi siswa kelas VIII yang berjumlah 32 orang dengan tujuan membentuk karater kemandian pada siswa. Adapaun metode yang digunakan dalam kegiatan ini meliputi bebrapa tahap, yaitu tahapan persiapan, tahap pelaksanaan kegiatan, dan tahap monitoring dan evaluasi. Hasil dari kegiatan pengabdian kepada masyarakat ini menunjukkan adanya peningkatan pengetahuan peserta didik kelas VIII SMPN 4 Ungaran mengenai penanganan cedera olahraga, khususnya cedera ankle, dengan menggunakan metode RICE (Rest, Ice, Compression, Elevation). Berdasarkan data evaluasi sebelum dan sesudah pelatihan, diperoleh hasil sebagai berikut: Jumlah peserta dengan kategori baik meningkat sebesar 59,3%, jumlah peserta dengan kategori cukup mengalami penurunan sebesar 46,8%, dan jumlah peserta dengan kategori kurang mengalami penurunan sebesar 12,5%. Berdasarkan hasil kegiatan yang telah dilaksanakan, dapat disimpulkan bahwa kegiatan edukasi dan pelatihan mengenai penanganan cedera ankle dengan metode RICE berhasil meningkatkan pengetahuan siswa kelas VIII di SMPN 4 Ungaran. Pelatihan ini efektif dalam mengubah pemahaman peserta dari kategori kurang dan cukup menjadi kategori baik.